Longitudinal trends in e-cigarette devices used by Californian youth, 2014–2018. (September 2020) - Lin, Crystal; Baiocchi, Mike; Halpern-Felsher, Bonnie
Highlights: E-cigarette use increased from 14.1%−46.2% (2014–2018). Most new e-cigarette smokers endorsed using JUUL and/or another pod e-cigarette. In 2018 most new e-cigarette smokers endorsed JUUL or another pod e-cigarette use. Abstract: The rate of adolescent and young adult (AYA) e-cigarette usage has increased in recent years, possibly due to the introduction of sleek new e-cigarette devices such as JUUL. This study analyzed data from 400 California AYA to examine trends in e-cigarette usage by device type (disposables, large-size rechargeables, vape/hookah pens, JUUL/pod-based). Participants were asked about their ever, past 30-day, and past 7-day use of e-cigarettes; their usual e-cigarette device used; and co-use of devices in seven surveys administered approximately biannually from 2014 to 2018. During this time period, total e-cigarette ever-usage in our cohort increased linearly from 14.1% to 46.2% (ptrend < 0.001). JUUL/pod-based e-cigarette ever-usage increased from 14.9% to 22.5% in just six months in 2018. Furthermore, a majority of new e-cigarette users at the time of the survey endorsed using JUUL/pod-based devices (58.3% in Wave 6, 73.0% in Wave 7). With newer device options, AYA were also increasingly less likely to endorse older models such as disposables (19.1% to 6.9% from 2014 to 2018, ptrend < 0.01) and rechargeables (69.1% to 26.2% from 2014 to 2018, ptrend < 0.001) as their usual e-cigarette device. Participants who used JUUL/pod-based only as their usual device were more likely to endorse using only JUUL/pod-based devices during follow-up survey (70%), and none switched to a new device completely. Overall, this study provides a snapshot of how AYA's e-cigarette preferences appear to respond to new devices entering the market.